Evaluation of Sweet Pepper (Capsicum annum L.) Varieties as Influnced by Nitrogen Levels in Chitwan, Nepal - Lohani, Santosh; Sharma, Moha Dutta; Shah, Shree Chandra; Shrestha, Arjun Kumar (Nepalese Horticulture, 2020)
An experiment was conducted to assess the performance of sweet pepper varieties as influenced by nitrogen levels from August 2014 to February 2015 at Mangalpur, Chitwan. The experiment was laid out in two factorial Randomized Complete Block Design (RCBD) with three replications having sixteen treatments. Varieties and levels of nitrogen significantly affected growth, yield and qualitative parameters of fruits. Hybrid Indra and NS 632 performed better than open pollinated varieties viz. Sagar and California Wonder. Days to fifty percent flowering of NS 632 were earlier than California Wonder. Indra variety had the highest plant height (52.18 cm), number of secondary branches per plant (13.51) from 250 kg N/ha through chemical fertilizer while number of leaves per plant was higher in NS 632 variety (57.22) than Sagar variety (47.37). Indra variety showed the highest fruit weight (87.59 g) and total yield (39.45 t/ha) but NS 632 variety produced more number of fruits per plant (9.25) than California Wonder variety. This study showed that sweet pepper yield of hybrid varieties applied with 250 kg N/ha through chemical fertilizer was appropriate dose to get optimum yield under Chitwan condition.